Tense and aspect in the Wolof verb system - (:unkn) unknown (My University, 2016)
Wolof has a remarkable aspectual system with two levels of organization: (1) the basic verbal system is organized into inflectional paradigms expressing polarity and focus features. These basic conjugations share a common perfective value and have the speech moment as tense locus. Perfective aspect is therefore the unmarked value and is analyzed here as an aspectual by-product of the conjugation’s core meaning. It is induced by three different configurations depending on each conjugation’s semantics: resulting state for the Perfect, temporal presupposition entailed by focusing conjugations, and minimal structuring and a comprehensive view of the process for the Null tense and Presentative. These three configurations converge in a common ‘perfective effect’ when contrasted with the derived imperfective forms. (2) These primary conjugations enter into secondary oppositions by means of aspectual and temporal suffixes, thus imperfective and past reference are derived from the bare (perfective) conjugations by suffixation. The imperfective suffix has a functional competitor in the construction with a copula. This predicative variant probably signals an ongoing grammaticalization process involving spatial deictics. The imperfective suffix and its predicative variant are used to produce two distinct future tenses. They also combine to form imperfective compound conjugations referring to occasional events. Alongside the expected aspectual and temporal effects, the imperfective suffix also has noteworthy interclausal and modal effects. More generally, the Wolof verbal system reveals a general mechanism conditioned by Aktionsarten: with stative verbs, aspectual phasing shifts from a temporal to a modal level and expresses epistemic modality (certainty vs. uncertainty).
Keywords: African Research